THE INFLUENCE OF PATIENT SAFETY CULTURE AND HEALTHCARE WORKERS' BURNOUT ON THE QUALITY OF CLINICAL SERVICES - Bayu Kharisma; Farida Yuliaty; Vip Paramarta; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aimed to examine the influence of patient safety culture and healthcare worker burnout on clinical service quality. This study employed a quantitative cross-sectional design. Data were collected through a structured questionnaire distributed to healthcare workers involved in direct patient care. The study variables included Patient Safety Culture (X₁), Healthcare Worker Burnout (X₂), and Clinical Service Quality (Y). Data were analyzed using multiple linear regression. Instrument validity and reliability tests were conducted, followed by classical assumption tests, including normality, linearity, multicollinearity, heteroscedasticity, and autocorrelation tests. The findings indicated that all questionnaire items were valid and reliable. The classical assumption tests confirmed that the regression model met the required assumptions. The t-test results showed that Patient Safety Culture had a positive and significant effect on Clinical Service Quality, while Healthcare Worker Burnout had a negative and significant effect on Clinical Service Quality. The F-test demonstrated that Patient Safety Culture and Healthcare Worker Burnout simultaneously had a significant effect on Clinical Service Quality. The coefficient of determination (R²) was 0.479, indicating that 47.9% of the variation in Clinical Service Quality could be explained by the two independent variables.